Role of Muscle Morphology in Jumping, Sprinting, and Throwing Performance in Participants With Different Power Training Duration Experience. - Methenitis, Spyridon K; Zaras, Nikolaos D; Spengos, Konstantinos M; Stasinaki, Angeliki-Nikoletta E; Karampatsos, Giorgos P; Georgiadis, Giorgos V; Terzis, Gerasimos D (J Strength Cond Res, 2016)
The aim of the study was to examine the correlation between muscle morphology and jumping, sprinting, and throwing performance in participants with different power training duration experience. Thirty-six power-trained young men were assigned to 3 groups according to the length of their power training: less experienced (<1 year), moderately experienced (1-3 years), and experienced (4-7 years). All participants performed countermovement and squat jumps, 60-m sprint, and shot throws twice. Lean body mass (LBM) was evaluated with dual-energy x-ray absorptiometry and thigh muscle cross-sectional area (CSA) with anthropometry. The vastus lateralis architecture and fiber type composition were evaluated with ultrasonography and muscle biopsies, respectively. When all subjects were considered as 1 group (n = 36), jumping performance was correlated with LBM, fascicle length, and type II fiber CSA; sprinting performance was correlated with estimated thigh muscle CSA alone; and shot throwing was correlated with LBM and type I, IIA fiber CSA. In the least experienced group, the LBM of the lower extremities was the most significant contributor for power performance, whereas in the moderately experienced group, the LBM, architectural properties, and type II fiber percentage CSA were the most significant contributors. For the experienced group, fascicle length and type II fiber percentage CSA were the most significant factors for power performance. These data suggest that jumping performance is linked with muscle morphology, regardless of strength or power training. The vastus lateralis muscle morphology could only partially explain throwing performance, whereas it cannot predict sprinting performance. Power performance in experienced participants rely more on the quality of the muscle tissue rather than the quantity.
Keywords: Absorptiometry, Photon; Adolescent; Adult; Athletic Performance; Body Composition; Exercise; Exercise Test; Humans; Male; Muscle Fibers, Fast-Twitch; Quadriceps Muscle; Resistance Training; Running; Time Factors; Ultrasonography; Young Adult